Critical urban cosmopolitanism and the governance of urban diversity in European cities. (January 2018) - Raco, Mike
This paper draws on the findings of a cross-national European Union project, named DIVERCITIES, that analyses the relationships between narratives and meanings of the term 'diversity' and their influence on the governance and planning of European cities. It is widely argued that there is a growing dissonance between the policy narratives and agendas found in metropolitan cities and amongst national governments. The former are characterised as being more pragmatic, tolerant and open in their approaches than the latter who, in many instances, have adopted more assimilationalist and nationalist rhetorics and policies. In exploring these governance dynamics, the paper builds on the work of Delanty to argue for a methodological approach grounded in what he terms critical cosmopolitanism, or a focus on the dynamic interactions between global and local influences on governmentalities and policy priorities. Much of the writing on critical cosmopolitanism has focused on questions of identity. This paper expands the concept and assesses its applicability to understandings and interpretations of urban politics and governance, through the lens of diversity narratives and the ways in which they are 'fixed' to broader political projects by regimes in different contexts. It argues that a range of meanings are being attached to 'diversity'. In some instances, the term acts as a focus for more progressive forms of intervention. In others, however, it is being used to justify divisive forms of growth politics or acts as a lightning rod for existing discontents. The paper concludes by reflecting on the impacts of recent anti-globalisation and immigration politics across Europe and the fragility of existing fixes and policy assumptions.